Treatment-Resistant Depression in America Latina study: one-year follow-up of treatment resistant depression patients under standard of care reveals insights on quality of life, disability, work impairment, and depressive symptoms - Recco, Kelen; Bonetto, Gerardo Garcia; Lupo, Christian; Nardi, Antonio E.; Morales, Arnulfo; Becerra-Palars, Claudia; Perocco, Sergio; Pfau, Alanna (Frontiers in Psychiatry, 2023)
Introduction Depressive Disorders are on the rise worldwide. This is also the case in Latin America (LatAm). Treatment-Resistant Depressive Disorder (TRD) poses additional burden to patients with depression. Impacts quality of life (QoL) and other dimensions, and standard of care (SOC) is insufficient to achieve the desired clinical outcomes. Evidence from LatAm is, however, lacking. The present study was devised as a 1-year follow-up of the SOC in TRD patients in LatAm to explore the burden of TRD. Methods This was an observational, multinational, longitudinal study. Patients with clinical diagnosis of TRD in LatAm were included in a 1-year follow-up with SOC. Beyond the Sociodemographic characterization, outcome measures were QoL (EQ-5D-5L), disability (Sheehan Disability Scale - SDS), work productivity (Work Productivity and Activity Incapacity Questionnaire: depression - WPAI:D) and depression severity (Patient Health Questionnaire-PHQ9). Patients were assessed every 3-months and comparison was performed based on change from baseline to each visit and end of study (EOS - 12 months). Results Patients averaged 48 (± 13.12) years, mostly female (80.9%) and married/consensual union (42.5%) or single patients (34.4%). Despite the SOC treatment, three-quarters of the patients remained symptomatic at EOS, regardless of the significant longitudinal decrease (p ≤ 0.001). Similar trends were found for disability (p ≤ 0.001) -82.2% of the patients reporting work/school disruption at EOS-, percentage of work (34%) and activity impairment (40%) at EOS (p ≤ 0.001) and only 29.2% of patients with depressive severity “none” at EOS (p ≤ 0.001). The results portray the need to improve clinical outcomes in this complex and burdensome disease in LatAm. Discussion Here we show that the burden of TRD remains significant in essential dimensions of everyday life at EOS underlining the need for better therapeutic solutions. The improvements in most patients do not provide the desired outcome of return to the state before the condition. Further research should focus on identifying which treatments provide better outcomes in a real-world context.